More young adults accidentally pregnant; neither timed nor wanted: evidence from Southwest Ethiopia - Mulugeta, Sharew; Tilahun, Tizta; Admasu, Bitiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In the resource-poor setting, unintended pregnancy is exacerbated by several factors that result in high maternal and newborn deaths. Given the considerable gap between actual and wanted fertility rates in Ethiopia, preventing unintended pregnancy can play a role in reducing complications, morbidity, and mortality. The purpose of this study was to determine unintended pregnancy and its correlates among ever pregnant women in Bitta woreda, Southwest Ethiopia. Methods: Quantitative data from a community-based cross-sectional study among 770 ever- pregnant women (15-49 years) were employed. A random selection using multistage sampling technique was exercised to select study participants. Logistic regression models were used to asses factors associated with unintended pregnancy. Results: In the study area nearly, thirty-seven percent of women have experienced an unintended pregnancy: mistimed (26%) and unwanted (11%). Three percent of the respondents had a faced an induced abortion. A relatively higher proportion of women aged 26-29 years reported experiencing unwanted and mistimed pregnancies. Women who traveled a longer distance (more than an hour) to family planning service area were more likely to face unintended pregnancy (AOR=2.23(1.37-3.63)). A woman who had more than five parity were more likely to experience unintended pregnancy 5.52(2.50-12.20). Conclusions: The unintended pregnancy remains higher in the study area which is more than the national average. Existing unintended pregnancy among young women urges family planning providers to deliver youth-inclusive family planning programs.